O autista na clínica psicanalítica - Lins , João Barretto de Acioly (2024)
In thiswork, I investigatethecontributionsofpsychoanalysistounderstandingclinical management ofautisticpeople. I seektounderstandhowtheunconsciousisconstitutedaccordingto Sigmund Freud andthesubjectoflanguageaccordingto Jacques Lacan, as well as toinvestigatethegenealogyofautism in thefieldofpsychiatryandpsychoanalysis, to examine theconstitutionoftheautisticsubject in psychoanalysisand, finally, toresearchtheimportanceoftransference in clinical management withautisticchildren.At first, thisresearchwasbibliographical in nature, withtheaimofanalyzingcontentthrough a literature review oftheworksof Sigmund Freud, Jacques Lacan, Leo Kanner, Rosineand Robert Lefort, Collete Soler, Marie-Christine Laznik, Jean-Claude Maleval, Alfredo Jerusalinsky, Inês Catão andAngelaVorcaro. In thecourseofmystudies, I used data analysisbasedonreadingthetexts. The analysisofresults, however, does notworkwiththesignification, butratherwiththesignifier, aimingtoact as a methodthatseekstheemptyingofmeaningand a possiblechange in signification. Thisisbecausethepsychoanalyticclinic, insteadoffocusingonthemeaningalreadyattributed, involvestheanalyst in listeningtothesignifiers in ordertoquestioncrystallizedmeanings. The analyst, in turn, does notimpose a prior meaningandavoidsinterpretingfromanestablished ideal. In writingthisresearch, I readvariousclinicaldiaries, which are observationsandwritingsmadebypsychoanalysts in theirworkwithautisticchildren, adolescentsandadults.In thefirstchapterofthiswork, I trytoexplaintheconstitutionofthesubject in psychoanalysisbyinvestigatingtheconceptsofunconscious, drive andrepression, whichunderpinthemetapsychologicaltripodofFreud'sthought. I thenillustratethestructuringofthe self accordingtoFreudiantheory, andfinally move ontostudythesubjectaccordingtoLacan'stheory.In thesecondchapter, I present a studyonthegenealogyofautism in thefieldofpsychiatryandpsychoanalysis, reflectingontheproblemof diagnoses and, finally, I investigatetheunderstandingoftheautisticsubjectaccordingtopsychoanalysis. Finally, I concludewithananalysisoftheimportanceoftransference in thepsychoanalyticclinicwithautisticpeople.